2020
DOI: 10.14710/ijred.9.2.227-235
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Synthesis of Lignin Derivatives from <em>Acacia mangium </em>to Improve the Enzymatic Hydrolysis of Kraft Pulp Sorghum Bagasse

Abstract: The present study is aimed at optimizing the synthesis of Amphipilic lignin derivatives (A-LD) from the isolated lignin of A.mangium black liquor (BL), using the one and two step acid isolation method, and commercial lignin (LS) was used as comparison. The experimental design was conducted using Taguchi method, which consisted of four parameters and two level factors, with reference to the matrix orthogonal array, L8, including temperature, reaction time, amount of polyethylene glycol diglycidylethers (PEGDE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
8
0
3
Order By: Relevance
“…The addition of A-LD in enzymatic hydrolysis has been found to successfully increase the reducing sugar yield (RSY) of SSB kraft pulp up to 81%. Another study on the optimization of A-LD synthesis conditions also confirmed the beneficial effects of the RSY (Fatriasari et al 2020a). The lignin derivatives addition was effective to increase RSY on several pretreated biomass containing low lignin content (Fatriasari et al 2020b).…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…The addition of A-LD in enzymatic hydrolysis has been found to successfully increase the reducing sugar yield (RSY) of SSB kraft pulp up to 81%. Another study on the optimization of A-LD synthesis conditions also confirmed the beneficial effects of the RSY (Fatriasari et al 2020a). The lignin derivatives addition was effective to increase RSY on several pretreated biomass containing low lignin content (Fatriasari et al 2020b).…”
Section: Introductionmentioning
confidence: 64%
“…The precipitated lignin was stored in a freezer at −18 °C for 24 h and filtered by a technical paper filter. The lignin powder was obtained after drying the precipitate at 45 °C for 24 h. The A-LD was synthesized according to the optimization condition by Fatriasari et al (2020a). The lignin stock was prepared by dissolving 1 g of lignin in 50 mL NaOH (1 mol/L).…”
Section: Preparation Of the Kraft Pulp And A-ldmentioning
confidence: 99%
See 2 more Smart Citations
“…Lignin is usually mixed with polyethylene to produce bio-surfactant. For instance, blending kraft-lignin with polyethylene glycol diglycidyl ethers (PEDGE) successfully enhanced enzymatic hydrolysis for bioethanol production, and the reducing sugar yield increased about 20% besides of lignin-derivative biosurfactant (Fatriasari et al 2018;Fatriasari et al 2020). In another report, acetic lignin was reacted with PEDGE under atmospheric pressure, which reduced the amphiphilic viscosity to less than 0.3 dl/g and was effectively used as a cellulose stabilizer (Uraki et al, 2001).…”
Section: Chemical Reaction To Produce Lignin-based Bio-surfactantmentioning
confidence: 99%